Low tidal volume ventilation strategy and organ functions in patients with pre-existing systemic inflammatory response - Vanya Chugh; Asha Tyagi; Vandna Arora; Abhay Tyagi; Shukla Das; Gargi Rai; Ashok K Sethi (Wolters Kluwer Medknow Publications, 2019)
Background and Aims: Ventilation can induce increase in inflammatory mediators that may contribute to systemic organ dysfunction. Ventilation-induced organ dysfunction is likely to be accentuated if there is a pre-existing systemic inflammatory response. Material and Methods: Adult patients suffering from intestinal perforation peritonitis-induced systemic inflammatory response syndrome and scheduled for emergency laparotomy were randomized to receive intraoperative ventilation with 10 ml.kg-1 tidal volume (Group H) versus lower tidal volume of 6 ml.kg-1 along with positive end-expiratory pressure (PEEP) of 10 cmH2O (Group L), (n = 45 each). The primary outcome was postoperative organ dysfunction evaluated using the aggregate Sepsis-related Organ Failure Assessment (SOFA) score. The secondary outcomes were, inflammatory mediators viz. interleukin-6, tumor necrosis factor-α, procalcitonin, and C-reactive protein, assessed prior to (basal) and 1 h after initiation of mechanical ventilation, and 18 h postoperatively. Results: The aggregate SOFA score (3[1-3] vs. 1[1-3]); and that on the first postoperative day (2[1-3] vs. 1[0-3]) were higher for group L as compared to group H (P < 0.05). All inflammatory mediators were statistically similar between both groups at all time intervals (P > 0.05). Conclusions: Mechanical ventilation with low tidal volume of 6 ml/kg-1 along with PEEP of 10 cmH2O is associated with significantly worse postoperative organ functions as compared to high tidal volume of 10 ml.kg-1 in patients of perforation peritonitis-induced systemic inflammation undergoing emergency laparotomy.